(untitled) (Mongolian Journal of Agricultural Sciences, 2020)
In this paper, we studied growth and biomass of 1-2 years old Siberian elm seedlings grown in the tree nursery, near Ulaanbaatar, Mongolia. Ulmus pumila L. has a wide natural distribution throughout the country. Due to climate change and other factors, environmental degradation has become inevitable in the country and efforts to restore degraded land are made in different regions. Due to its drought and cold resistance, Siberian elm is considered to be one of the most suitable species of tree to be used for restoration and windbreaks. We measured height, diameter and biomass of 1-2 year old seedlings, and composed allometric equation to estimate aboveground and belowground biomass. Equations have high prediction power (R2=0.80-0.96), however, they are more suitable to seedlings and saplings due to difference in the allometric relationship of trees at different ages. We also explored relationship between diameter (at root collar) and height, which was fairly good (R2=0.73). In order to be able to use the equation to indirectly estimate belowground biomass of seedlings, we estimated Root/shoot ratio of seedlings. Root/shoot ratio was 0.85 for 1-2-year-old seedlings. Belowground biomass estimation can be useful in determining how well the tree can fix soil around it, and draw water and nutrients from the soil. The result of the study can be used for further work concerning the viability of Siberian elm for restoration and windbreaks.